Comparison between RSA hardware and software implementation for WSNs sexcurity schemes - Md. Tap, Abu Osman; Manttoro, Teddy; Alkalbani, Abdullah Said (2010)
The need of security to protect the data through networks has become of vital importance and critical for many sensor network applications. There are several security schemes implemented using hardware or software trying to solve the problem of security in WSN by taking into consideration the limitations of sensors (bandwidth and energy), the majority of them are symmetric key encryption schemes and some others are asymmetric encryption schemes is not recommended to be used because of high time complexity and consumption demand. In this study we compare the time complexity and power consumption between software and hardware implementation using RSA algorithm. Our simulation shows that usage of hardware security could improve time efficiency and decrease the power consumption, so the strong cryptography can be implemented in WSNs security.